The Role of “Makan Besamo” in Cultural Integration and Family Education : It is Impact on family Discipline and Communication in the Jambi Community - Fahmi Rohim; Darma Putra; Try Susanti; Dian Syafitrah; Mardiana Mardiana (Universitas Muhammadiyah Enrekang, 2024)
This study explores the role of Makan Besamo (shared meals) in the integration of culture and family education, with a specific focus on its impact on family discipline and communication within the Jambi community. Makan Besamo, a traditional practice where families gather for communal meals, serves as an important cultural ritual that fosters togetherness, strengthens familial bonds, and instills values of respect and discipline. This qualitative research employs a mixed-methods approach, including in-depth interviews, observations, and surveys with families in the Jambi region. Findings reveal that Makan Besamo not only promotes cultural preservation but also enhances family communication, creating a platform for open dialogue and mutual understanding among family members. Additionally, the practice contributes significantly to the development of family discipline, as it reinforces collective responsibility, time management, and shared values. The study highlights the importance of incorporating cultural practices such as Makan Besamo in modern family education to strengthen social cohesion, improve interpersonal relationships, and ensure the continuity of cultural heritage. The results underscore the role of traditional practices in shaping family dynamics and fostering positive social behavior within the community.